Effect of No Space Exercises in the Context of Resistance Band Training on BMI of College Students: Exploring the Impact of Resistance Band Training on BMI of College Students (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Ancient days there were frequent yogic, martial art practices, conference, but during this century these types of regular practices for people are happening once in a blue moon. The researcher wants to spice up the activity for all in a paradigm and provide them fitness with opulent opportunities. For doing regular physical exercise, people required a voracious appetite for fitness and beauty consciousness. Physical fitness is very necessary for healthy and tension free life. Fitness training also includes diet and good sleep. People are always complaining that, there is “no space and time” for exercise this paper gives a direction to manage these limitations. Here, researcher illustrated the beneficial effects of the resistance activity in our life. Exercise programs in this paper describe the changes of a BMI for college sedentary women. For that, the purpose of the study was to find out the effect of band resistance exercise to know the changes in, the groups. In-order to serve this purpose 25 sedentary female subjects who were selected from college of engineering, Thrissur and they were under gone two month training programme. The age of subjects’ ranges from 18 to 22.Paired sample T-test statistical techniques used. In all these statistical tests, level of significance was fixed 0.05 levels. All statistical analysis was carried out with the help of statistical package SPSS 16.0 for WINDOW. The central value obtained from T- distribution with 59 degrees of freedom at level at level 0.05 is 1.96. Experimental group the mean (BMI) the pretest and post test scores are 28.12 and 20.96, its mean difference is 7.16.The calculated T -value is 11.63.Since T greater than the tabulated value, there is a statistically significance from pre to posttest mean difference score. Based on the analysis it is concluded that the effect of resistance band exercises, significantly decreased (BMI) variable of sedentary females.